What does global migration network say about recent changes in the world system structure?. Issue 3 (5th August 2014) - Gilbert Ahamer, Professor Glenn Hardaker, Dr; Zinkina, Julia; Korotayev, Andrey
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The aim of this paper is to investigate whether the structure of the international migration system has remained stable through the recent turbulent changes in the world system. Design/methodology/approach – The methodology draws on the social network analysis framework – but with some noteworthy limitations stipulated by the specifics of data. Findings – The list of the most central nodes demonstrates remarkable stability over time, with the USA consistently occupying the first place and Russia and Germany stably entering the top-five (or even top-three ever since 1990). Centrality analysis also clearly demonstrates the emergence (in the 1970s) and development of the Gulf countries (particularly Saudi Arabia and UAE) as major migration destinations. Research limitations/implications – The results of the analysis present a mixture of evidence to support both the principles of the neoclassical migration theory, and some of its critiques, as the migration patterns are strongly influenced by historical links (such as colonial ties), geographical distance, cultural distance, etc. Defining the scope of influence of each of these factors lies beyond the scale of this paper. However, further application of social network analysis to studying the global migration network, in the authors' opinion, has quite remarkable potential for contributing to this line of research. Originality/value – The paper views the specific features in the structure of the global migration network and their implications for world system studies.